Educación financiera en comerciantes informales de la ciudad de Loja - Tillaguango Tillaguango, Jhenrry Leonidas (2022)
The present investigation was developed considering the need to provide financial education to informal merchants in the city of Loja, in order to impart knowledge and tools necessary for the administration of their personal finances. In this context, the general objective of the study is to design a financial education plan for informal merchants in the city of Loja. The study was descriptive through a quantitative approach, as an instrument for collecting information a survey was used, which was adapted from the financial knowledge measurement questionnaire proposed by the Organization for Economic Cooperation and Development (OECD). ), which in turn was developed by the International Network for Financial Education (INFE), the population under study was made up of 242 merchants determined randomly. The results determined that the target population has a regular level of financial knowledge according to the rating scale that is designed in the methodology, representing 60.35%, demonstrating weaknesses in the application of mathematical calculations, which is why it was necessary to propose a program of financial education in order to improve the weaknesses found. After the training days, it was shown that the informal merchants reached a positive variation of 14.55% in the percentage scale of qualifications, going from a fair to a good level. Finally, it is concluded that the financial education program contributed positively to the improvement of financial knowledge in terms and application of mathematical calculations, turning weaknesses into strengths.